Assessment of Oral Mucosal Changes by Ultrasonography and Color Doppler in Oral Submucous Fibrosis: A Case-Control Study - Binindita Mondal Bhunia; Vaishali M Rajashekar; David M Priscilla; Govindaraju Roopashri; Vijayalakshmi Nandini; Poojya Ramdev (Wolters Kluwer Medknow Publications, 2023)
Background: Oral submucous fibrosis (OSMF) is an insidious chronic disease involving any part of the oral cavity. As ultrasonography (USG) facilitates imaging of a wider area, it can be a valuable tool to determine the severity of this disease. Objective: With this background, this study was undertaken to assess oral mucosal changes by ultrasonography and color Doppler in OSMF. Materials and Methods: The sample size included 40 subjects between 20 and 60 years inclusive of either gender, divided into group 1 (controls) and groups II, III, and IV (OSMF cases). The submucosal thickness of buccal mucosa and upper and lower labial mucosa was measured by USG followed by analysis of submucosal vascularity by color Doppler. The data were subjected to statistical analysis. Results: It was found that all the subjects had normal submucous thickness and normal vascularity in group 1 (controls). In group II to group III to group IV cases, there was an increase in submucosal thickness and a decrease in submucosal vascularity as the stage of OSMF progressed and the results were statistically significant. Conclusion: USG and color Doppler were able to demonstrate an increase in the thickness of the submucosal layer and a decrease in submucosal vascularity with the progression of OSMF. Hence, USG assessment of OSMF can supplement with other modalities for monitoring disease progression.